Gólyamese - Dobray, György (Hungary : Hollósi, Zsuzsanna G. ; Varga, Gábor ; Dobray, György, 2005)
Open adoption means that the biological mother does not want or cannot bring up her unborn child, whom she entrusts into the care of adopting parents whom she herself knows and accepts. This film is about the sometimes shocking and dramatic process of open adoption. The waiting, the nerve-racking and joyful minutes, hours and weeks of preparation, the tribulations of the adopting family. And of course the struggle the mother goes through whether she should give up altogether, and whether she is capable of giving up what is the most sacred for every parent: their own child. The participants of open adoption are not enemies. They are simply mothers who make a decision in order to protect the child.
Duration: 00:56:00
Keywords: Documentary films